Tuskegee's Truths: Rethinking the Tuskegee Syphilis Study - Landman, W. A. (Journal of medical ethics, 2002)
No one interested in the ethics of biomedical research will have failed to hear about the Tuskegee syphilis study, or, to give it its full title, the US Public Health Service's Tuskegee Study of Untreated Syphilis in the Negro Male. This study, conducted from 1932 to 1972, on black (African American) males in Tuskegee, Alabama, has, with complete justification, become the paradigm of moral depravity in the field of biomedical research. Virtually every rule of good, ethical research was broken during this “research” over a period of 40 years, down to denying participants even the knowledge, let alone the option, of a remedy when it became available.In recent years, the Tuskegee syphilis study has received renewed public attention, for two reasons. First, in 1996, 24 years after …